Pembuatan Koagulan Cair Dari Lempung Gambut Untuk Pejernihan Air - Yunita Selonika; Jhon Armedi Pinem; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Clay is one of the abundant natural resources and have not been used optimally. Value for clays can be improved further. Utilization of clay as a source of liquid coagulant is one way of increasing value of the clay. The aim of research was to make liquid coagulant from clay peat with extraction process and determine the percentation of extraction. The powdered clay was calcined at a temperature of 750oC for 1 hour extracted using sulfuric acid for 60, 90 and 120 minutes at a temperature of 95°C. The slurry was filtered to obtain the filtrate which was a liquid coagulant. Liquid coagulant extracted during the process of 120 minutes has the highest of percent aluminum and iron extraction.Key words : coagulant, coagulation, extraction, peat clay